Patient Satisfaction Outcomes after Robotic Arm-Assisted Total Knee Arthroplasty: A Short-Term Evaluation - Marchand, Robert C.; Sodhi, Nipun; Khlopas, Anton; Sultan, Assem A.; Harwin, Steven F.; Malkani, Arthur L.; Mont, Michael A. (The Journal of Knee Surgery, 2017)
Robotic arm-assisted total knee arthroplasty (RATKA) presents a potential, new added value for orthopedic surgeons. In today's health care system, a major determinant of value can be assessed by patient satisfaction scores. Therefore, the purpose of the study was to analyze patient satisfaction outcomes between RATKA and manual total knee arthroplasty (TKA). Specifically, we used the Western Ontario and McMaster Universities Arthritis Index (WOMAC) to compare (1) pain scores, (2) physical function scores, and (3) total patient satisfaction outcomes in manual and RATKA patients at 6 months postoperatively. In this study, 28 cemented RATKAs performed by a single orthopedic surgeon at a high-volume institution were analyzed. The first 7 days were considered as an adjustment period along the learning curve. Twenty consecutive cemented RATKAs were matched and compared with 20 consecutive cemented manual TKAs performed immediately. Patients were administered a WOMAC satisfaction survey at 6 months postoperatively. Satisfaction scores between the two cohorts were compared and the data were analyzed using Student's t-tests. A p-value < 0.05 was used to determine statistical significance. The mean pain score, standard deviation (SD), and range for the manual and robotic cohorts were 5 ± 3 (range: 0–10) and 3 ± 3 (range: 0–8, p < 0.05), respectively. The mean physical function score, SD, and range for the manual and robotic cohorts were 9 ± 5 (range: 0–17) and 4 ± 5 (range, 0–14, p = 0.055), respectively. The mean total patient satisfaction score, SD, and range for the manual and robotic cohorts were 14 points (range: 0–27 points, SD: ± 8) and 7 ± 8 points (range: 0–22 points, p < 0.05), respectively. The results from this study further highlight the potential of this new surgical tool to improve short-term pain, physical function, and total satisfaction scores. Therefore, it appears that patients who undergo RATKA can expect better short-term outcomes when compared with patients who undergo manual TKA.
Keywords: orthopedic; TKA; RATKA; score; outcome